Original Higgs inflation and phantom crossing - Shahrokh Assyyaee; Nematollah Riazi (European Physical Journal C: Particles and Fields, 2019)
Abstract It is a standard practice to ignore the initial kinetic term in an inflationary analysis. Here, we overrule this practice to analyze pre-inflationary, inflationary and post-inflationary dynamics of the original Higgs-inflation model from a wider view. To this end, our calculations are not restricted to slow-roll regime. Perhaps, the most interesting result that we have found is the behavior of the field trajectories which begin their way from a phantom origin, before reaching a quasi de Sitter partial attractor. Both analytical and numerical calculations ultimately confirm that for the original Higgs inflation scenario the mentioned de Sitter path ends in an oscillatory phase which is the required condition for having (p)reheating. This achievement discriminates the current research from the previous studies about the late time phantom crossing scenarios which often end in a de Sitter future world. This confirms that a phantom energy epoch may deliver much more than has been thought earlier. In our calculations, we have employed the dynamical system method and explain the results both analytically and through the plotted numerical calculations. Beside the present results, the dynamical system approach can be used in other studies which deal with non-minimal gravity models. Reducing the number of dynamical variables to two enables us to enjoy the two dimensional phase diagram which is very elusive.